Political Organization in the Pskov Republic: the Prince, the Veche and Sovereignty - Arakcheev, Vladimir (Quaestio Rossica, 2014)
The article analyzes the socio-political organization of the Pskov Veche republic in the 13th–15th centuries, particularly the changes in personnel and in competences of the Pskov princes, the authority and the officials of the princely administration. The article shows the evolution of the sotnia (a hundred unit) organization from the princely one into the republican one. The research reveals Pskov’s considerable differences from Novgorod in terms of regulation of commerce and defines the function of the rank-and-file traders’ elder in the system of the republican power. The author argues that the Pskov veche functioned as a state institution that had been formed in the course of Pskov’s fight for independence in the 13th century. The fact of adopting the documents of taxpaying at the veche assembly reveals the fully institutionalized character of governmental bodies of the Pskov republic. By drawing upon H. J. Berman’s argument of independence within European cities of the 11th–12th centuries, this article contributes to the discussion of Pskov’s independence by outlining the main criteria of Pskov’s sovereignty. Pskov had a right to issue and supplement laws; the Pskov Judicial Charter arose out of the princes’ local charters and was further edited at the veche assembly. Pskov set its own taxes and the veche was empowered to free separate groups of landowners from paying taxes. The rights to military mobilization, to the declaration of war and to making peace, which were under the complete jurisdiction of the republic, undoubtedly demonstrates the sovereignty of Pskov. Finally, the sovereignty of Pskov was manifested in the symbols of stamps and coins that were used in the Pskov republic. All these facts taken together demonstrate the feasibility of applying the medieval European cities’ criteria of sovereignty to the Pskov socio-political realties.